ECONOMIC ACTIVITY AND NATURAL GAS AS A POTENTIAL DESTABILIZER OF THE SLOVENIAN ECONOMY - Festiđ, Mejra; Repina, Sebastijan; Kavkler, Alenka (Journal of Energy Technology, 2024)
This article empirically investigates whether natural gas has the potential of destabilizing the Slovenian economy. The resultscon firmedtheindirectrelation,thattheincreaseofgasprices decelerates the dynamics of aggregate domestic consumption, which further decelerates activities in individual industries. An empirical analysis has proven that the natural gas does have the potential off orecasting production trends in individual industries with in the Slovenian economy. By using the dynamics of natural gas price movements (and other explanatory variables),we can for ecastthe dynamics of move ments in the production of textiles,leather,fur andclothes,rubberͲandplasticͲbasedproducts,metals,furniture,as well as in the processing industry,recycling,electricity,naturalgas,steamandhotwatersuppliesinSlovenia.